2011
DOI: 10.3111/13696998.2011.627404
|View full text |Cite
|
Sign up to set email alerts
|

Association of cinacalcet adherence and costs in patients on dialysis

Abstract: This study demonstrated that low adherence to cinacalcet, which may be associated with undesirable clinical and health-economic outcomes, is common. Despite limitations inherent in retrospective studies of claims databases, such as unobserved confounding, non-discrimination between prescription fill and actual use, and not knowing the reasons for non-adherence, these results suggest that inpatient cost savings of $8899, more than offset higher medication costs of $5858 associated with increased cinacalcet adhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 23 publications
0
24
0
1
Order By: Relevance
“…2,3 Unfortunately, poor adherence with prescribed medications is a widely recognized problem in dialysis patients due to the complexity of the regimen and lifelong duration of therapy. 2,4,5 A recent systematic literature review found that more than half of the included studies reported nonadherence rates of ≥ 50% in the ESRD population. 5 High out-of-pocket costs borne by patients can be a deterrent to therapeutic adherence and, therefore, to the effectiveness of prescribed medications.…”
Section: ■■ Methods Data Sourcementioning
confidence: 99%
“…2,3 Unfortunately, poor adherence with prescribed medications is a widely recognized problem in dialysis patients due to the complexity of the regimen and lifelong duration of therapy. 2,4,5 A recent systematic literature review found that more than half of the included studies reported nonadherence rates of ≥ 50% in the ESRD population. 5 High out-of-pocket costs borne by patients can be a deterrent to therapeutic adherence and, therefore, to the effectiveness of prescribed medications.…”
Section: ■■ Methods Data Sourcementioning
confidence: 99%
“…This effect was further evidenced by the ICER of approximately $56,000 per QALY and the ICER of approximately $116,000 per QALY associated with assumptions of the lag-censoring effect estimates (20% improvement in mortality) and the unadjusted ITT effect estimate (6% improvement in mortality). The lag-censoring analysis assumes adherence to cinacalcet and is therefore not fully representative of the real world in which adherence to cinacalcet and other oral drugs is known to decrease over time [31]. Excluding costs of commercial cinacalcet from the conventional therapy arm increased the ICER to approximately $90,000 per QALY, highlighting the sensitivity of the model to the overall costs of cinacalcet, which was also seen as one of the major sources of variance in the one-way sensitivity analysis, whereas including stroke (an important outcome not included in the primary composite end point of EVOLVE) did not materially change the ICER.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, nonadherence to cinacalcet varies: 45.6%-71%. [46][47][48] Gincherman et al investigated the refill-based adherence rate for cinacalcet in 79 hemodialysis patients, and found a 1-year medication-possession rate .80% (indicating consistent medication use) of 29% for cinacalcet. 46 The authors hypothesized that the lower adherence rate with cinacalcet had been the result of the high incidence of gastrointestinal side effects.…”
Section: Drug Adherence With Oral Cinacalcetmentioning
confidence: 99%